24 ReSPECT (recommended summary plan for emergency care and treatment) in a pandemic: the impact of COVID-19 on advance care planning in a UK University hospital cardiology department. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Copley, A; West, M; Morris, J; Hargreaves, F; Tayebjee, MH
Abstract : Background: Acute hospital clinicians play a key role in initiating discussions around advance care planning (ACP). Despite a widespread agreement that ACP is beneficial and facilitates patient-centred decision making, ACP prevalence in the acute hospital setting can be sporadic. COVID-19 created a heightened awareness of the need for early decision-making, in order to ensure patients received appropriate treatments, based on their general health, personal values and individual wishes. Methods: A retrospective study of patients admitted to a tertiary UK hospital Cardiology department during two discrete time periods; December 2019 and April 2020. Data was collected from electronic records and compared for significant differences between groups. This included the completion of ReSPECT forms, age, co-morbidities, frailty score and discharge diagnosis. Results: The study included 164 patients in total. There was no significant difference in age, co-morbidities or frailty between the groups. ReSPECT form completion significantly increased from December 2019 to April 2020 (9/84 (11%) vs 39/80 (49%); p < 0.0001). 25/26 (94%) of COVID-19 positive patients had evidence of ReSPECT form discussion. For individuals with non-COVID-19 diagnoses, 14/54 (26%) had evidence of ReSPECT form discussions. Conclusions: There was a statistically significant improvement in ACP during the first wave of COVID-19. Factors influencing this are likely to include heightened public and professional awareness of healthcare resources, an acknowledgement for rapid deterioration in patients with COVID-19, increased media coverage around the necessity for early decision-making, and a subsequent increase in patient expectation to discuss ACP. COVID-19 provides the opportunity to better establish meaningful ACP into acute hospital practice in the future. Further work is needed to assess the quality of the ACP process and individual patient experience. Increased familiarity with ACP, at both a public and professional level, could lead to enduring improvements in the facilitation of conversations and patient-centred decisions.